A study on the transformational leadership of madrasah principals from the perspective of educators and educational staff - Mulyadi, Mus; Sobri, Muhamad; Sobri, Muhamad (Edelweiss Applied Science and Technology, 2024)
This study aims to understand the perceptions of teachers and educational staff regarding the transformational leadership style of Madrasah Principals in Bengkulu Province, Indonesia. The study uses a descriptive research design with several variables: Madrasah level, position within the Madrasah, teacher expertise, educational qualifications, work experience, and gender. To achieve this goal, the researcher designed a questionnaire consisting of 6 indicators and 17 question items, distributed electronically at random from 03-02-2024 to 18-08-2024, with a total of 615 respondents. The results of the study indicate that the transformational leadership of Madrasah Principals in Bengkulu Province can be concluded as a leadership style that motivates teachers and educational staff, enabling them to grow and achieve optimal performance. The transformational leadership in these madrasahs is also characterized as charismatic, where subordinates place trust in their leaders. Additionally, the principals have successfully directed the staff to act in alignment with the shared goals. Furthermore, the principals have stimulated enthusiasm among subordinates for individual and group tasks, as well as addressing issues at hand. The madrasahs in Bengkulu Province have developed rapidly and have become a source of pride for the community. Madrasahs with transformational leadership are expected to maintain the quality of the institution, the vision and mission, and its flagship programs, thereby strengthening the quality of religious education for the younger generation.